2021
DOI: 10.1088/1755-1315/782/3/032068
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity and effect of gamma ray irradiation on upland rice CV. Sidikalang

Abstract: Improvement efforts to obtain high yield and adaptive varieties can be carried out through plant breeding programs. The success of irradiation in increasing population diversity is determined by plant radiosensitivity. Radiosensitivity aimed to determine a dose that caused plant death (lethal dose) or growth inhibition of 50% of the irradiated population (LD-50). The seeds of rice CV. Sidikalang was irradiated with gamma rays at doses of 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100 and 1200 Gy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…A negative effect of higher doses or concentrations of mutagens on germination percentage in rice was determined by Gowthami et al (2017) citing disruptions at the cellular level (physiological or physical level) and chromosomal damage as possible causes. A similar finding was also made by Naibaho et al (2021), who stated that the highest level of rice germination occurred at radiation doses of 100-400 Gy and the lowest at a dose of 700 Gy, while there was no germination at doses of 800 Gy and above. The results showed that gamma irradiation had greater impact on seedling growth compared to germination process.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…A negative effect of higher doses or concentrations of mutagens on germination percentage in rice was determined by Gowthami et al (2017) citing disruptions at the cellular level (physiological or physical level) and chromosomal damage as possible causes. A similar finding was also made by Naibaho et al (2021), who stated that the highest level of rice germination occurred at radiation doses of 100-400 Gy and the lowest at a dose of 700 Gy, while there was no germination at doses of 800 Gy and above. The results showed that gamma irradiation had greater impact on seedling growth compared to germination process.…”
Section: Resultssupporting
confidence: 83%
“…This reduction of growth could be explained by the effects of irradiation on the signalling pathway of growth regulatory factors and cell oxidation at the highest irradiation doses (Wi et al, 2007). Naibaho et al (2021) also stated that plant height decreased with higher irradiation doses with reduction up to 46.51% at 600 Gy. The efficiency of mutation breeding will be higher if the optimal dose of radiation is determined, which will lead to an increase mutation frequency and will not significantly threaten the survival and reproduction of plants (Hong et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The rice seeds of the Sidikalang cultivar (M3) used were generated by Naibaho et al (2020) with an LD-50 value of 586.45 Gy, so the radiation dose used was 0 Gy, 200 Gy, 400 Gy, and 600 Gy.…”
Section: Methodsmentioning
confidence: 99%